Etika v praksi - izločanje in vstavljanje urinskih katetrov - Šmitek, Jana (Obzornik zdravstvene nege, 2004)
The present article presents ethical issues related to holistic patient care. Our decisions and actions are lead by the principle of not hurting in general,also when inserting urine catheters. Ethical dilemmas related to urinecatheter insertion are presented. The most ethically scrutinized questionis routine insertion of urine catheters to the elderly who can not take any decisions about themselves, and in whom nurses are often the main initiators for such solution of elimination problems.
Keywords: Ethics, Nursing; Etika zdravstvene nege; medicinska etika; Medicinska sestra-bolnik, odnosi; Nurse-Patient Relations; Nursing Process; Urinary Catheterization; Urinska kateterizacija; urinski katetri; urologija; zdravstvena nega; Zdravstvena nega, proces